2021
DOI: 10.1038/s41598-020-80496-7
|View full text |Cite
|
Sign up to set email alerts
|

Early age at menarche and metabolic cardiovascular risk factors: mediation by body composition in adulthood

Abstract: Evidence suggests that early menarche increases cardiometabolic risk, and adiposity would be a possible mediator of this association. We assessed the association between age at menarche and metabolic cardiovascular risk factors and estimated the indirect effect of body composition in adulthood. In 1982, all hospital births in the city of Pelotas/Brazil, were identified and live births were examined and have been prospectively followed. At 30 years, information on age at menarche and metabolic cardiovascular ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 51 publications
2
23
2
1
Order By: Relevance
“…Other reproductive factors, such as early menarche age, was also the study interest in some studies. For example, Bubach et al suggested that early menarche age may lead to higher prevalence of metabolic cardiovascular risk factors, but this effect was partially mediated by body composition (26). The mechanism behind the influence of early menarche on metabolic health profile may be attributable to endogenous estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Other reproductive factors, such as early menarche age, was also the study interest in some studies. For example, Bubach et al suggested that early menarche age may lead to higher prevalence of metabolic cardiovascular risk factors, but this effect was partially mediated by body composition (26). The mechanism behind the influence of early menarche on metabolic health profile may be attributable to endogenous estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…El IMC desde la niñez hasta la edad adulta puede ser objeto de intervención por la posible relación de la edad de menarquia con la adiposidad, sobre todo en las mujeres con menarquia temprana, aunque aún faltan estudios que expliquen el mecanismo subyacente 277 . Otros estudios sugieren que la intervención preventiva a los 14 años en PC y el IMC en niñas con menarquia temprana haría desaparecer la asociación entre OB y factores metabólicos hasta la adultez, sugiriendo que el efecto de la menarquia temprana y el aumento del RCV está mediado por la composición corporal en la edad adulta 277 , 278 .…”
Section: Factores De Riesgo Emergentesunclassified
“…A history of early onset of menarche (at or before the age of 11) is associated with increased cardiovascular risk factors, including a more unfavorable lipid panel (specifically, higher TC, LDL and TG) [ 8 , 9 ] later in life at middle to older ages, as well as increased future CVD risk [10] . As elevated body mass index is one risk factor for early onset of menarche, prevention of childhood obesity and improved cardiovascular health of children and adolescents is paramount.…”
Section: Life Cyclementioning
confidence: 99%